Effects of state-wide implementation of the Los Angeles Motor Scale for triage of stroke patients in clinical practice - Stefanie Behnke; Thomas Schlechtriemen; Andreas Binder; Monika Bachhuber; Mark Becker; Benedikt Trauth; Martin Lesmeister; Elmar Spüntrup; Silke Walter; Lukas Hoor; Andreas Ragoschke-Schumm; Fatma Merzou; et al. (Neurological Research and Practice, 2021)
Abstract Background The prehospital identification of stroke patients with large-vessel occlusion (LVO), that should be immediately transported to a thrombectomy capable centre is an unsolved problem. Our aim was to determine whether implementation of a state-wide standard operating procedure (SOP) using the Los Angeles Motor Scale (LAMS) is feasible and enables correct triage of stroke patients to hospitals offering (comprehensive stroke centres, CSCs) or not offering (primary stroke centres, PSCs) thrombectomy. Methods Prospective study involving all patients with suspected acute stroke treated in a 4-month period in a state-wide network of all stroke-treating hospitals (eight PSCs and two CSCs). Primary endpoint was accuracy of the triage SOP in correctly transferring patients to CSCs or PSCs. Additional endpoints included the number of secondary transfers, the accuracy of the LAMS for detection of LVO, apart from stroke management metrics. Results In 1123 patients, use of a triage SOP based on the LAMS allowed triage decisions according to LVO status with a sensitivity of 69.2% (95% confidence interval (95%-CI): 59.0–79.5%) and a specificity of 84.9% (95%-CI: 82.6–87.3%). This was more favourable than the conventional approach of transferring every patient to the nearest stroke-treating hospital, as determined by geocoding for each patient (sensitivity, 17.9% (95%-CI: 9.4–26.5%); specificity, 100% (95%-CI: 100–100%)). Secondary transfers were required for 14 of the 78 (17.9%) LVO patients. Regarding the score itself, LAMS detected LVO with a sensitivity of 67.5% (95%-CI: 57.1–78.0%) and a specificity of 83.5% (95%-CI: 81.0–86.0%). Conclusions State-wide implementation of a triage SOP requesting use of the LAMS tool is feasible and improves triage decision-making in acute stroke regarding the most appropriate target hospital.